Nanocrystalline Silicon Oxide Emitters for Silicon Hetero Junction Solar Cells. (August 2015) - Mazzarella, Luana; Kirner, Simon; Gabriel, Onno; Korte, Lars; Stannowski, Bernd; Rech, Bernd; Schlatmann, Rutger
Abstract: In this study we developed a hydrogenated nanocrystalline silicon oxide (p)nc-SiOx :H as an emitter window layer for silicon heterojunction solar cells. We investigated the variation of refractive index and crystalline volume fraction at different growth conditions by Plasma Enhanced Chemical Vapor Deposition (PECVD) and we show that combining a low refractive index (n ∼ 2.65) and low parasitic absorption the (p)nc-SiOx :H emitter can replace the standard (p)a-Si:H, which leads to a short circuit current increase of up to 4%. We also show a method to reduce the incubation layer thickness in the initial stage of growth using a CO2 plasma treatment of the intrinsic amorphous layer surface prior to the emitter deposition. Lifetime measurements prove that the plasma treatment and the emitter layer deposition did not compromise the passivation layer quality. Moreover, in order to improve the p-emitter/n-type TCO contact, a highly doped nc-Si:H layer is implemented on top of the emitter, which leads to lower series resistance (Rs, light ) and higher fill factor (FF) without affecting the open circuit voltage (Voc ).